1978
DOI: 10.1002/aic.690240105
|View full text |Cite
|
Sign up to set email alerts
|

Combined pressure and diffusional transition region flow of gases in porous media

Abstract: Expressions were derived for combined pressure and diffusional transition region flow of gases in porous media. Experimental systems were developed to verify the applicability of the equations for packed columns of Kaolinite clay and quartz sand with methane and carbon dioxide flowing into nitrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

1980
1980
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…However, the tortuosities of our suite of Mars-analog soils are very consistent with measurements of unconsolidated particulate materials (Hoogschagen, 1955;Currie, 1960b;Alzaydi et al, 1978;McKay et al, 1998). Indurated or heavily compacted soils may be more tortuous, but our measurements imply a rough upper limit of ∼2.5 on the tortuosity of unconsolidated dry soils, with values between 1.5 and 2 being more typical.…”
Section: All Soilssupporting
confidence: 70%
See 1 more Smart Citation
“…However, the tortuosities of our suite of Mars-analog soils are very consistent with measurements of unconsolidated particulate materials (Hoogschagen, 1955;Currie, 1960b;Alzaydi et al, 1978;McKay et al, 1998). Indurated or heavily compacted soils may be more tortuous, but our measurements imply a rough upper limit of ∼2.5 on the tortuosity of unconsolidated dry soils, with values between 1.5 and 2 being more typical.…”
Section: All Soilssupporting
confidence: 70%
“…First, the PPM is computationally the simplest model to apply to laboratory, climate, and permafrost studies, but offers no disadvantages in terms of accuracy (Satterfield, 1970). Second, the PPM has been successfully applied to laboratory studies spanning a wide range of pressure and temperature conditions, and all modes of diffusion (e.g., Johnson and Stewart, 1965;Satterfield and Cadle, 1968;Youngquist, 1970;Satterfield, 1970;Alzaydi et al, 1978). Third, a parallel path formalism has typically been applied to diffusive problems in the Mars literature (e.g., Clifford and Hillel, 1983;Jakosky, 1993, 1995).…”
Section: Mass Transport In Porous Solidsmentioning
confidence: 99%
“…Corey (1994) reasons that for a continuum analysis, the fluid particles must be small compared with the pore dimensions and large compared with the mean-free-path of the fluid molecules. Alzaydi and Moore (1978) and McWhorter (1990) have shown that under most conditions the assumption of a continuum should not have a large impact on the results. The VapourT numerical model assumes a static soil-water system.…”
Section: Soil Vapor Extraction Numerical Modelmentioning
confidence: 96%
“…Gas flow measurement performed by Alzaydi and Moore (1978) showed that Darcy's law could provide a fair approximation of gas flow in a low permeability material. Furthermore, Izadi and Stephenson (1992) confirmed that in contrary to coarse grain soils, the gas slippage flow through low permeable soils decreased as the degree of saturation decreased.…”
Section: Gas Transport Due To Advectionmentioning
confidence: 99%